The Influence Of Leadership And Financial Compensation On Teacher Spirit Of Pujut 1 Junior High School Central Lombok - Alfiatul Maulina; Saripudin Serif (Universitas 45 Surabaya, 2024)
This study aims to determine the effect of leadership and financial compensation on teacher morale at SMP Negeri 1 Pujut, Central Lombok Regency. The type of research used in this study is causal associative research using a quantitated . The data collection method used is the census method. The population in this study were all teachers at SMP Negeri 1 Pujut, Central Lombok Regency, totaling 48 people. Data analysis using multiple linear regression analysis. The results of the study show that: 1. Leadership has a positive and significant effect on teacher morale at Pujut 1 Public Middle School, Central Lombok Regency. 2. Financial compensation has a positive and significant effect on teacher morale at Pujut 1 Public Middle School. The leadership coefficient value is greater, indicating that the influence of leadership is stronger on work morale.